Socioeconomic Factors Associated with Stunting Among Children in Selawangi Village, Indonesia - Faseha, Dzuliani; Nurlaila, Nurlaila; Hamdan, Ahmad (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
In Selawangi Village, there were 34 cases of stunting. This study aimed to determine the socioeconomic conditions of families with stunted children in Selawani Village. The data were collected through interviews, observation, and documentation. The data analysis method applied a qualitative descriptive method through data collection, data reduction, data presentation, and drawing conclusions. Sampling used purposive sampling. Based on the results of the study, the socioeconomic factors of families with stunted children indicated that the families are primarily from farm laborer families. The parents only attended elementary school and earned less than the regional minimum wage. They rent a house with electricity. Most of them still use traditional sanitation systems. Not all families have vehicles and cell phones. A low income will hinder a child from growing and developing optimally since their family's income mainly determines a child's nutritional intake.